LITERATURE REVIEW ANALYSIS OF THE IMPLEMENTATION OF THE COOPERATIVE LEARNING MODEL TYPE STAD IN SCIENCE LEARNING IN ELEMENTARY SCHOOLS - Ameliya Dwi Saputri; Renita Tiara Sari; Sheren Kurnia Taufani (Teaching and General Education Studies, 2025)
This research is a qualitative study employing a literature review approach to address the lack of teachers' understanding of available learning models, particularly the STAD (Student Teams Achievement Divisions) cooperative learning model in elementary science education. The study aims to analyze the effectiveness of the STAD cooperative learning model in improving learning outcomes, critical thinking skills, and student motivation. The research method involves a literature review of ten journal articles discussing the application of the STAD cooperative learning model in elementary science education. The findings indicate that the STAD cooperative learning model has a positive impact, especially in higher grade levels. Overall, implementing the STAD cooperative learning model in elementary science education offers several benefits, including improving learning outcomes (70%), enhancing critical thinking skills (20%), and increasing learning motivation (10%).